2022
DOI: 10.1097/aci.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis across Europe: are pollen food syndrome and lipid transfer protein allergy so far apart?

Abstract: Purpose of reviewTraditionally pollen-food syndrome (PFS) is considered to be a mild cross-reacting food allergy affecting only Northern Europe, with lipid transfer protein (LTP) allergy being more severe and mainly occurring in Southern Europe. This review seeks to update the reader on both types of plant food allergy and to determine whether the stereotypical presentations of these plant food allergies remain the same, with a particular focus on reaction severity. Recent findingsRecent findings suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This association of nsLTP sensitization with asthma severity has not been described elsewhere. This may result, at least partially, from the high geographical variation in the prevalence of nsLTP sensitization 19–21 . Sensitization toward nsLTP from pollen and food was observed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This association of nsLTP sensitization with asthma severity has not been described elsewhere. This may result, at least partially, from the high geographical variation in the prevalence of nsLTP sensitization 19–21 . Sensitization toward nsLTP from pollen and food was observed.…”
Section: Discussionmentioning
confidence: 98%
“…This may result, at least partially, from the high geographical variation in the prevalence of nsLTP sensitization. [19][20][21] Sensitization toward nsLTP from pollen and food was observed. It is yet to be determined whether sensitization to nsLTP primarily occurs through pollen or food exposure.…”
Section: Sensitization To Certain Single Components Is Associated Wit...mentioning
confidence: 95%
See 1 more Smart Citation
“…The proteins have cross-reacting nature. 12,13 The impressive study by Baseggio et al 8 also showed that anaphylaxis is caused by different foods in the different regions of the world. Recent epidemiological data indicate that Black children have higher rates of food allergy relative to other racial/ethnic groups.…”
Section: Food Anaphylaxismentioning
confidence: 99%
“…LTPs, widespread distributed in the plant kingdom and also are responsible for number of food‐induced anaphylactic reactions. The proteins have cross‐reacting nature 12,13 …”
Section: Food Anaphylaxismentioning
confidence: 99%